ICC 2019 - 2019 IEEE International Conference on Communications (ICC) 2019
DOI: 10.1109/icc.2019.8761983
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Source Coded Downloads

Abstract: In this paper, we propose a selective-repeat (SR) automatic repeat-request (ARQ) model for multi-source download scenarios and analyze their useful throughput that we refer to as goodput. The multi-source scenario comprises a set of transmitters that send packets to a receiver. We characterize the forward channels from the transmitters to the receiver via a general hidden Markov model (HMM) and assume that the reverse channels from the receiver to the transmitter are lossless. To find the average goodput of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…We use this to compare amount of received packets that increase the DoF at the client to all received packets. We also compared our measurement results to our previous work [8], where we construct a model to analyze multi-source networks. Our analysis and our measurements show similar trends.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We use this to compare amount of received packets that increase the DoF at the client to all received packets. We also compared our measurement results to our previous work [8], where we construct a model to analyze multi-source networks. Our analysis and our measurements show similar trends.…”
Section: Resultsmentioning
confidence: 99%
“…It sends a packet from a generation that has the least received DoF and in transiting packets. We chose this method of scheduling a generation for sending because it has already shown potential to improve throughput in RLNC enhanced distributed systems [8].…”
Section: B Coded Mutpmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we extend our previous works on coded multisource download [15], [21]. We propose two protocols for multi-source download and evaluate their goodput through measurements.…”
Section: A Main Contributionsmentioning
confidence: 96%
“…We have previously shown that Random Linear Network Coding (RLNC) [14] may also be used to improve the throughput of a multi-source network [15]. RLNC creates linear combinations of the original packets using random coefficients.…”
Section: Introductionmentioning
confidence: 99%